Assessing yield, quality, water use efficiency and profitability of forage crops in rainfed agricultural management systems - Baral, Rudra Bahadur (Kansas State University, 2023)
Forage production is an integral part of the livestock industry as it significantly impacts animal performance, including body weight gain, reproduction, and milk production. Moreover, it is one of the key contributors to the agricultural economy of the United States. However, despite its high demand and economic value, the yield and production of forage crops have not improved in the last two decades. Unpredictable weather events such as erratic rainfall and periodic drought, reliance on traditional wheat-based cropping systems, and failures in various management aspects including crop and variety selection, irrigation management, and delays in planting and harvesting are the primary factors that influence forage dry matter yield (DMY) and forage nutritive value (FNV). Considering these factors, the first chapter of this dissertation estimated the yield gap in major alfalfa-producing states of the United States. County-level yield and weather data were collected from 393 counties in 12 major rainfed alfalfa-producing states and estimated attainable yield (Ya) using frontier function analysis, water-limited potential yield (Yw) and water use efficiency (WUE) using boundary function analysis, and major yield-limiting factors using conditional inference tree. This study estimated the Ya of 9.6+1.5 Mg ha⁻¹, resulting in a mean yield gap of 34%, and Yw of 15.3+3 Mg ha⁻¹, resulting in a mean yield gap of 58%. The potential WUE was 30 kg ha⁻¹ mm⁻¹. The CIT analysis revealed that the rainfall and minimum temperature during the growing season were the primary weather variables influencing rainfed alfalfa production. This study provides a better understanding of the difference in yield levels observed in rainfed alfalfa production across major alfalfa-producing states, suggesting potential for further improvement through better management practices. The methodologies used in this study could be useful for many other countries that don't have research-based data to estimate crop yield and yield gaps. The second chapter explored alternative summer forage crops for wheat-based rainfed cropping systems in Kansas. A three-year field experiment was conducted, comparing seven different crop sequences and intensities. The results showed the variability in DMY, WUE, FNV and profitability across crops, growth stages, and planting times. Crops planted at optimum planting dates demonstrated higher DMY, while those planted late exhibited higher FNV. Forage soybean had the highest DMY (13.9 Mg ha⁻¹) followed by soybean and alfalfa. Soybean, alfalfa and forage soybean had an excellent FNV, with crude protein (CP) above 18% and relative feed value (RFV) exceeding 150. The WUE varied among crops, with cowpea demonstrating the highest efficiency (26.8 kg mm⁻¹). Forage soybean and cowpea were recommended as potential summer annual forage crops, considering their DMY, WUE, FNV and net farm income. The findings of this study provide valuable insights into appropriate crop selection, efficient management of planting and harvesting times, and strategies to enhance yield, quality, and profitability within forage production systems. The third chapter evaluated the impact of water regimes, maturity stages, and subsequent cuttings on DMY and FNV in alfalfa production. Different varieties were planted under drought, rainfed, and irrigation conditions, and DMY and FNV were evaluated at different growth stages. The results indicated that DMY and FNV were influenced by soil water availability, production year, and maturity stages. Drought-stressed alfalfa showed lower DMY but higher FNV. The delayed harvesting resulted in lower DMY but higher RFQ under drought conditions and higher DMY but lower RFQ under irrigation. Early harvesting led to lower yields but higher protein content and digestibility. Both conventional and lower-lignin varieties performed equally in terms of yield and forage quality. The financial analysis indicated that alfalfa is a highly profitable crop, with an estimated profit margin ranging from 52 to 64% per hectare under different soil moisture conditions. The study provides valuable information for alfalfa producers to make informed decisions about harvesting time and irrigation investments.
Keywords: Forage dry matter yield; Forage nutritive value; Relative feed value; Water use efficiency; Net farm income; Rainfed cropping systems